Tinjauan Pelaksanaan Pengumpulan, Validasi dan Verifikasi Data Rekam Medis Pasien Jaminan Kesehatan Nasional (JKN) Rawat Inap Guna Mendukung Pelaporan Eksternal (RL 4a dan RL 5) di RSUD Ratu Zalecha Martapura - Ulfa Sukmasari; Zainal Abidin; Noor Huda (HB PRESS, 2017)
Delay in the return of medical records after discharge from the inpatient room. Lack of medical record data is validated and verified prior, the medical records of outpatient and inpatient care for the created external reports. The purpose of this research is to review the implementation of the collection, validation and data verification of patient medical record inpatient national health insurance to support the reporting of external (RL 4a and RL 5) in Ratu Zalecha Martapura Hospital. This research is a descriptive study, population in this study the medical records of patients JKN in Ratu Zalecha Martapura Hospital period January-March 2016 as many as 2159 medical records. The sample in this study is the medical records of patients hospitalized JKN totaled 96 inpatient medical records with the Slovin formula. The result of this research were reporting lines at the Ratu Zalecha Hospital Martapura is appropriate only delay the collection of medical records, reporting at the Ratu Zalecha Martapura Hosiptal in the medical record data collection practices were in accordance with the applicable SOP but there is still a delay in the collection of medical records, the process of collecting data from the room to UKRM not timely and data is not valid, external reporting and verification (RL 4a and RL 5) has not been made and there are some data that have not been validated